Juventude da agricultura familiar e seu retorno para o campo: trajetória de jovens de Francisco Beltrão - Paraná - Celuppi, Daniela (2021)
This dissertation deals with the investigation carried out in the interior of the city of Francisco Beltrão, with young family farmers who returned to the countryside, after a period of work and living in the urban environment. The research goes against the grain of much of the research that discusses young people, relating them to migration to urban centers. Thus, the target audience was young family farmers from the municipality of Francisco Beltrão, located in the Southwest Region of Paraná, associated with the Union of Workers and Workers in Family Farming – SINTRAF, affiliated to the Federation of Workers in Family Farming of State of Paraná – FETRAF-PR and the National Confederation of Workers in Family Farming in Brazil – CONTRAF. The general objective of the research was to analyze the factors that motivate the return, to the rural space, of young people from family farming in the city of Francisco Beltrão – PR. The methodological instruments used for data collection were questionnaires, interviews and theoretical analysis on the subject. As a result, it is noteworthy that the choice for life in rural areas is not restricted solely to professional or income reasons, but is based on the way of life, on personal links with the place, on quality of life, that is, it has a value that goes far beyond monetary. Thus, it is understood that family farmers, especially young people who remain in the field or, especially in the case of this research, those who return, create strategies that reduce the impact and the uncertainties that the rural space sometimes presents to them.